Comparison Between Amaryl and Nut Grass (Cyperus rotindus L.) Rhizome Extract on Blood Sugar Levels of Male Mice (Mus musculus L.) Induced by Alloxan - Ayu Ayssca Besty Prastiwy; Hendri Busman; Nuning Nurcahyani (Jurnal Penelitian Pertanian Terapan, 2016)
Nut grass rhizome contains several chemical compounds including aetheric oil, flavonoid, saponine, and antidiabetic agents, where as amaryl is a chemical medicine used to treat diabetes.  A study about the comparison between amaryl and nut grass rhizome extract on blood sugar levels of male mice has been conducted.  The study aimed to determine the effect of nut grass rhizome extract compared to amaryl in decreasing the blood sugar levels of male mice.  The mice were divided into four groups of treatment, each group consists of six mice.  The mice were intraperitoneally induced by alloxan to induce diabetes with the dosage of 0,15 mg/40 gr BB, using 0,9% of  NaCl as solvent, before being given the medicine.  Later, the mice were given amaryl and the nut grass rhizome extract, they were group 1 as control :  amaryl 0,4 mg/40 gr BW in 0,4 ml/100 ml of aqua bidest, group 2:  nut grass rhizome extract 4,5 mg/40 gr BB in 0,4 ml/100 ml of aqua bidest, group 3:  nut grass rhizome extract 45 mg/40 gr BB in 0,4 ml/100 ml of aqua bidest, group 4:  nut grass rhizome extract 135 mg/40 gr BB in 0,4 ml/100 ml of aqua bidest.  The result showed that the mice given nut grass rhizome extract with the dosage of 135 mg/40 g BW had significantly decreased blood sugar level compared to amaryl.  This was the effect of flavoniod compound in the nut grass rhizome extract which was rich in antioxidants so it could decrease the blood sugar levels of the diabetic mice.Key words:  amaryl, nut grass rhizome extract, intraperitoneal, flavonoid, anti oxidants, diabetes.